2004
DOI: 10.1016/j.femsle.2004.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Lignin peroxidase is involved in the biobleaching of manganese-less oxygen-delignified hardwood kraft pulp by white-rot fungi in the solid-fermentation system

Abstract: Biobleaching of manganese-less oxygen-delignified hardwood kraft pulp (E-OKP) by the white-rot fungi Phanerochaete sordida YK-624 and P. chrysosporium was examined in the solid-state fermentation system. P. sordida YK-624 possessed a higher brightening activity than P. chrysosporium, increasing pulp brightness by 13.4 points after seven days of treatment. In these fermentation systems, lignin peroxidase (LiP) activity was detected as the principle ligninolytic enzyme, and manganese peroxidase and laccase activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…It has been suggested that MnP, LiP, and laccase produced extracellularly by white rot fungi are involved in the oxidative breakdown of lignin [38][39][40][41][42][43][44]. Therefore, these enzyme activities were determined during treatment of genistein with P. sordida YK-624 ( Fig.…”
Section: Treatment Of Genistein With White Rot Fungusmentioning
confidence: 99%
“…It has been suggested that MnP, LiP, and laccase produced extracellularly by white rot fungi are involved in the oxidative breakdown of lignin [38][39][40][41][42][43][44]. Therefore, these enzyme activities were determined during treatment of genistein with P. sordida YK-624 ( Fig.…”
Section: Treatment Of Genistein With White Rot Fungusmentioning
confidence: 99%
“…The white‐rot fungus Phanerochaete sordida YK‐624, which was isolated from rotted wood, exhibits greater ligninolytic activity and selectivity among beech woods than either Phanerochaete chrysosporium or Trametes versicolor (Hirai et al ., ). In a previous study, we demonstrated that P. sordida YK‐624 produces MnP (Hirai et al ., , ) and LiP (Sugiura et al ., ; Machii et al ., ; Hirai et al ., ) as ligninolytic enzymes.…”
Section: Introductionmentioning
confidence: 98%
“…The same unique nonspecific mechanisms that give these fungi the ability to degrade lignin also allow them to degrade a wide range of pollutants, thus conferring them a number of advantages not associated with other bioremediation systems (1). This has opened new prospects for the development of biotechnological processes aimed at the degradation of xenobiotic compounds (2), effluent decolorization (3,4), and pulp biobleaching (5,6).…”
Section: Introductionmentioning
confidence: 99%